Reactivity Trends of Fe Phthalocyanines Confined on Graphite Electrodes in Terms of Donor-Acceptor Intermolecular Hardness: Linear Versus Volcano Correlations - Zagal-Moya, J; Zagal-Moya, J; Espinoza-Vergara, J; Espinoza-Vergara, J (Elsevier, 2014)
In this work, we have studied the interaction between the hydrazine N2H4 molecule with several FeN4 macrocyclic complexes (FePc s). In order to modulate the electron density located on the metal center using iron-phthalocyanine (FePc) as the reference, we used substituted iron-phthalocyanines with different types of substituents electron-donating groups such as iron-tetraamino-phthalocyanine (4?(NH2)FePc) and iron-octamethoxyphthalocyanine (8?(OCH3)FePc), and with electron-withdrawing groups such as iron-tetranitrophthalocyanine(4?(NO2)FePc) and iron-hexadecachlorophthalocyanine (16(Cl)FePc), respectively. We have found that the energy of interaction between hydrazine and the Fe center in the macrocycle increases as the electron-withdrawing power of the substituents increases. When rate constants instead of currents are compared in a semilog plot versus ??D-A, a linear correlation is found where log k increases as the intermolecular hardness of the systems decreases. © 2014 Elsevier B.V. All rights reserved.